Profit-based unit commitment problem: A review of models, methods, challenges, and future directions - Abdi, Hamdi (Renewable & sustainable energy reviews, 2021)
The unit commitment problem is one of the most significant and basic issues in the monitor, control, and operation of modern power systems, which has always been a subject of great concern to researchers and operators as the most extensive human-made system. Before restructuring, one of the main objectives of unit commitment problem was the minimization of the total operation cost of power plants subject to various constraints, including unit and network ones. As the privatization and restructuring process became more serious, the primary purpose of the unit commitment problem has been changed to maximizing the total profit, which led to the emergence of a new concept known as profit-based unit commitment problem. Accordingly, the maximization of the profit for generation companies, all over the studied period, is a top-priority direction. This paper presents a comprehensive overview of the profit-based unit commitment problem in restructured power systems by investigating the most important studies on this topic and providing a complete classification. It also outlines the challenges facing researchers in this field, offers new insights, and suggests future directions. •Describing a comprehensive formulation for profit-based unit commitment problem.•Presenting a complete and comprehensive overview of profit-based unit commitment problem.•Reporting the used case study systems, simulation tools, hardware, and run-time.•Briefly reviewing the fitness functions, parameter setting, convergence criterion, and the obtained profit values.•Addressing the main challenging issues regarding the mentioned problem.